2023
DOI: 10.4143/crt.2022.264
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Overall Survival and Prognostic Factors in Patients with Lung Cancer: Results from the Korean Association of Lung Cancer Registry (KALC-R) 2015

Abstract: Purpose This study aimed to provide the clinical characteristics, prognostic factors, and 5-year relative survival rates of lung cancer diagnosed in 2015. Materials and MethodsThe demographic risk factors of lung cancer were calculated using the KALC-R (Korean Association of Lung Cancer Registry) cohort in 2015, with survival follow-up until December 31, 2020. The 5-year relative survival rates were estimated using Ederer II methods, and the general population data used the death rate adjusted for sex and age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…On the other hand, prior pulmonary TB remained independent factor associated with worse survival and confirmed our study result. For cancer subtype, small cell lung cancer, which was associated with higher mortality than non-small cell lung cancer, was similar as previous report ( 21 ). Under such high mortality in small cell lung cancer, the impact of prior TB might be masked and not significant.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand, prior pulmonary TB remained independent factor associated with worse survival and confirmed our study result. For cancer subtype, small cell lung cancer, which was associated with higher mortality than non-small cell lung cancer, was similar as previous report ( 21 ). Under such high mortality in small cell lung cancer, the impact of prior TB might be masked and not significant.…”
Section: Discussionsupporting
confidence: 91%
“…This high mortality can be attributed to two main reasons: late diagnosis and the inefficiency of the treatments available. Most of the patients present an advanced stage of the disease at the time of diagnosis, leading to an expected survival at 2 of 17 5 years below 10% [2][3][4][5]. Novel reliable, sensitive, and accurate diagnostic tests are required since early-stage identification is associated with longer life expectancy.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results have been reported also in research conducted in other geographical areas than ours. A study conducted by Da Som Jeon and colleagues on a South Korean cohort showed a better five-year survival for women with NSCLC, also stage-dependent [ 19 ].…”
Section: Discussionmentioning
confidence: 99%